Comparing two methods to assess power output associated with peak oxygen uptake in cyclists - Ronnestad, B. R. (The Journal of Strength and Conditioning Research, 2014)
The aim of this study was to compare 2 methods that are frequently used to calculate the power output (MAP) that is associated with peak oxygen uptake (VO2peak) in the exercise mode of cycling. One method calculates the MAP by extrapolation of the individual VO2 to submaximal power output relationships to the measured VO2peak (MAPDaniels), whereas the other method uses the minimal power output that elicits VO2peak during a graded VO2peak test (MAPBillat). Thirteen male competitive cyclists (VO2peak = 66 ± 5 ml/kg/min) performed 3 test sessions; first to determine MAPDaniels and MAPBillat; second and third sessions were used to measure the time to exhaustion during continuous cycling exercise to exhaustion (Tmax), time to 95% of VO2peak, and time > 95% of VO2peak with MAPDaniels and MAPBillat. Whether it was MAPDaniels or MAPBillat that was used on the second or third test session was randomized. There was no difference between mean MAPDaniels and mean MAPBillat (380 ± 38 vs. 383 ± 34 W, respectively) and their associated Tmax, time to 95% of VO2peak, and time > 95% of VO2peak during a Tmax test. In conclusion, this study did not find any difference between MAPDaniels and MAPBillat. The practical application of this study is that the choice of a method to calculate the MAP can be determined by practicality and that findings from studies using these 2 methods are comparable.